European Union requirements regarding criminal law and civil and administrative sanctions - Kert, Robert (European Integration Studies, 2025)
Directive (EU) 2024/1203 on the protection of the environment through criminal law was adopted on 11 April 2024 and must be implemented into national law until 21 May 2026. It brings the obligation to introduce a lot of new criminal provision to protect the environment comprehensively. The Directive does not only contain provisions on minimum maximum penalties for natural and legal persons, but also other sanctions and measures aimed at prevention and restoration of the environment. It is the task of the courts and authorities to find adequate reactions to a conduct which damages the environment.